2012
DOI: 10.4161/gmcr.19144
|View full text |Cite
|
Sign up to set email alerts
|

The VIRCA Project

Abstract: The VIRCA (Virus Resistant Cassava for Africa) project is a collaborative program between the Donald Danforth Plant Science Center, USA the National Crops Resources Research Institute, Uganda and the Kenya Agricultural Research Institute, Kenya. VIRCA is structured to include all aspects of the intellectual property, technology, regulatory, biosafety, quality control, communication and distribution components required for a GM crop development and delivery process. VIRCA's goal is to improve cassava for resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…It is, however, highly susceptible to CBSD. These qualities make TME 204 an ideal target for improvement within the VIRCA project, which aims to bring CMD- and CBSD-resistant planting material to smallholder farmers in East Africa (Taylor et al, 2012). We previously reported field resistance to CBSD generated from an inverted repeat construct carrying the CP of UCBSV (p718) (Ogwok et al, 2012; Odipio et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is, however, highly susceptible to CBSD. These qualities make TME 204 an ideal target for improvement within the VIRCA project, which aims to bring CMD- and CBSD-resistant planting material to smallholder farmers in East Africa (Taylor et al, 2012). We previously reported field resistance to CBSD generated from an inverted repeat construct carrying the CP of UCBSV (p718) (Ogwok et al, 2012; Odipio et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The Virus Resistant Cassava for Africa (VIRCA) project aims to utilize RNAi to generate and deliver cassava with enhanced resistance to CBSD to farmers in East Africa (Taylor et al, 2012). Proof of concept in cassava cv.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, the Virus Resistant Cassava for Africa (VIRCA) (Taylor et al, 2012) project at the Danforth Plant Science Center (St. Louis, MO, USA) recently organized a workshop to assess the risks and consequences of gene flow from transgenic cassava containing CBSV resistance to wild relatives. Based on existing information, this forum concluded that although gene flow is likely to occur, there is only a very small chance that this could lead to a reduction of genetic diversity in the germplasm pool (Hokanson et al, 2016).…”
Section: Regulations Of Genetically Modified (Gm) Crops In Developingmentioning
confidence: 99%
“…In view of the difficulties associated with conventional breeding, genetic engineering offers great potential for the rapid transfer of resistance genes to traditional cultivars, bypassing the possibility of the appearance of undesirable traits. Among the available biotechnological approaches, RNA interference (RNAi) or gene silencing technology, also called post-transcriptional gene silencing, offers significant potential for the control of CBSD Prins et al, 2008;Reddy et al, 2009) (Ezezika et al, 2012;Taylor et al, 2012). Three RNAi constructs targeting different parts of the CP of UCBSV-[UG:Nam:04] were generated, which consisted of the 894 nt (FL, full-length), 397 nt N-terminal (NT) and 491 nt C-terminal (CT) portions of the CP and expressed constitutively in the model host N. benthamiana (Fig.…”
Section: Genetic Engineering For Cbsd Resistancementioning
confidence: 99%